Russian Science and Technology Foresight – 2030: Key Features and First Results - Sokolov, Alexander; Chulok, Alexander (Foresight and STI Governance, 2012)
This paper reviews national features in the general evolution of science and technology (S&T) foresight over the last decade. Foresight has made a transition from thematic papers and policy briefs to a complex set of methods integrated in the framework of S&T and innovation policy making. Foresight also addresses broad social and economic issues along with conventional S&T problems. It focuses often on interdisciplinary fields and cross-sector problems. It has witnessed the introduction of such new methods as weak signals and wild cards, and it has benefitted from the integration of qualitative and quantitative approaches. Russian S&T foresight follows global trends. It has given support for revisions of the national S&T priorities and critical technologies. In 2007-2010, two cycles of the National S&T Foresight (initiated by the Ministry of Education and Science of the Russian Federation) were completed. They resulted in the creation of frameworks and expert networks for future studies. Foresight culture has been finding deeper roots in Russia. The paper addresses mainly the key features of the third (ongoing) cycle of the national S&T Foresight (2011) against the background of the first two cycles and the international trends. This cycle represents a wider coverage of issues (macroeconomic scenarios, trends in basic research, S&T resources, future demand for skills, and global drivers of S&T developments); more complicated methodologies (bibliometric analysis, expert panels, surveys, roadmapping, and quantitative models); and a combination of “market pull” and “technology push” approaches toward estimating future developments. This cycle is building a wider network of experts at new Foresight centres at various Russian research universities. It concludes with a discussion of some barriers still to be overcome in Foresight studies: integration of sectoral visions, deeper analyses of some scientific disciplines, stronger integration into policy making, and spreading among business and research communities.